Determining the impact of By-O-Reg plus in diets with or without feed grade antibiotic on growth performance of nursery pigs - Thomas, L. L.; Woodworth, Jason C.; Goodband, Robert D.; DeRouchey, Joel M.; Tokach, Michael D.; Dritz, Steven S. (My University, 2016)
A total of 717 nursery pigs (PIC C-29 × 28 and PIC L3 × 1040, initially 5.67 ± 0.05 kg BW) from 2 consecutive nursery groups were used in a 35-d growth study. The objective was to determine the impact of feeding increasing levels of By-O-Reg+ in diets with or without antibiotic on nursery pig growth performance. By-O-Reg+ is registered trademark of Advanced Ag Products, Hudson, South Dakota and is a unique mixture of essential oils primarily based on oregano. Dietary treatments were offered immediately after weaning at approximately 21 d of age and were organized in a 2 × 3 factorial with main effects of antibiotic (none vs. 55 mg/kg of Carbadox) and By-O-Reg+ (0, 0.05, or 0.10%). Experimental diets were fed for 21 d and then fed a common diet for the final 14 d. Pens of pigs (5 barrows and 5 gilts) were balanced by initial BW and randomly allotted to treatments with 12 pens/treatment. During the period when treatments were fed (d 0 to 21), there were no interactions observed between By-O-Reg+ and Carbadox but increasing By-O-Reg+ improved (quadratic, P = 0.016) G:F. Pigs fed diets with Carbadox had improved (P < 0.007) ADG, ADFI, and G:F. From d 0 to 35, there was an interaction (linear, P = 0.031) observed for ADFI with pigs fed diets without Carbadox having decreased ADFI as By-O-Reg+ level increased, whereas when pigs were fed diets containing Carbadox, ADFI increased with increasing By-O-Reg+. There were no main effects of By-O-Reg+ observed for the overall data; however, adding Carbadox for 21 d after weaning improved (P < 0.015) ADG, ADFI, and final BW and tended to improve (P < 0.087) G:F d 0 to 35. Overall, this study confirms the benefit of including a feed grade medication in nursery pig diets to improve growth performance. Increasing By-O-Reg+ in diets elicited few changes in performance, but during the test period the pigs fed 0.05% By-O-Reg+ had better G:F than those fed none or 0.10% By-O-Reg + .
Citation: Thomas, L. L., Woodworth, J. C., Goodband, R. D., DeRouchey, J. M., Tokach, M. D., & Dritz, S. S. (2016). Determining the impact of By-O-Reg plus in diets with or without feed grade antibiotic on growth performance of nursery pigs. Journal of Animal Science, 94, 83-83. Retrieved from <Go to ISI>://WOS:000375783900177
Keywords: Antibiotics; Nursery Pigs; Oregano; Agriculture